2018
DOI: 10.3390/su10051353
|View full text |Cite
|
Sign up to set email alerts
|

Sacrificial Pseudoreplication in LEED Cross-Certification Strategy Assessment: Sampling Structures

Abstract: Abstract:The study aims to suggest sampling structures to avoid sacrificial pseudoreplication in the evaluation of Leadership in Energy and Environmental Design (LEED)-certified projects. The sampling includes two structures that exclude sacrificial pseudoreplication and one structure that leads to sacrificial pseudoreplication: (i) The state is the sampling frame in which LEED projects are treated as primary sampling units; (ii) The US is the sampling frame, the state is the primary sampling unit in which LEE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 23 publications
(69 reference statements)
0
25
0
Order By: Relevance
“…This design structure can be defined as a single-unit design structure, in which the Mediterranean basin was defined at only one scale [30]. Recently, when LEED 2009 Silver-Gold transition was evaluated, a single-unit design was applied, either the entire United States or individual U.S. state [25]. It was clearly shown that corrected statistical conclusion occurred when the single-input design structure was applied to an individual U.S. state.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This design structure can be defined as a single-unit design structure, in which the Mediterranean basin was defined at only one scale [30]. Recently, when LEED 2009 Silver-Gold transition was evaluated, a single-unit design was applied, either the entire United States or individual U.S. state [25]. It was clearly shown that corrected statistical conclusion occurred when the single-input design structure was applied to an individual U.S. state.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the study [25], in the evaluation of LEED Gold-certified projects, the Mediterranean basin was defined as "a sampling frame" (i.e., the sampling frame is a collection of primary sampling units "accessible for sampling in the population of interest" [53]). While the LEED Gold-certified projects within each country (Turkey, Spain, and Italy) were defined as "primary sampling units" (i.e., the primary sampling unit is statistically independent of other primary sampling units within the same sampling frame [53]).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the third step, the normal distribution test is implemented because the number of samples of LEED silver, gold LEED, and LEED platinum projects is limited. Furthermore, the results of the Kolmogorov-Smirnov test showed that data is not a normal distribution, and LEED data are presented in ordinal scales [17]. To investigate the significant differences between the two groups with different LEED certificate levels of certification and consider the problem of pseudoreplication, the statistical tests used are based on suggestions of S. Pushkar's (2018) study [25].…”
Section: Discussionmentioning
confidence: 99%
“…Nguyen developed an application by interacting web map service (WMS) technology and BIM to pre-calculate LEED awarded points of the "Location and transportation" category [16]. The research of S. Pushkar (2018) pointed out that several data analysis studies of previous LEED-certified projects have to consider the problem of pseudoreplication [17]. Recently, when Wu et al (2017) [6] and Wu et al (2018) [18] analyzed previous LEED certification project data, they used aggregated processes to achieve extremely low P-values.…”
Section: Background Of Researchmentioning
confidence: 99%